Pelatihan Strategi Digital Marketing untuk UMKM di Desa Tanjung Beringin Kecamatan Pangkalan Kuras Kabupaten Pelalawan Provinsi Riau - Lismawati Ketra Pebriana (Tasnim Journal for Community Service, 2023)
The purpose of carrying out this community service activity with the theme Digital Marketing Strategy Training for UMKM in Pangkalan Kerinci City, Pelalawan Regency, Riau Province, is to provide knowledge about digital marketing and training in the application of digital marketing. The method used in carrying out this activity is through lectures and direct practice of implementing digital marketing. The stages of implementing this event include opening and introducing digital marketing, explaining digital marketing, explaining some of the problems that are often faced by MSMEs, explaining some foreign terms related to digital marketing, then continuing with practices related to digital marketing